2016
DOI: 10.21149/spm.v58i2.7797
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer

Abstract: Artículo especiAl P rostate cancer (PC) is the most common cancer and the leading cause of cancer death in men over 50 y in Mexico. In 2015, 41 210 cancer deaths are expected among men, 6 801 of which will be from PC.1 Prostate-specific antigen (PSA) has been applied as a useful marker for the early diagnosis and monitoring of PC. A randomized study in Europe demonstrated a progressive decrease in prostate cancer mortality, with a 51% reduction in individuals up to 75 years old who underwent screening.2 As the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 21 publications
0
32
0
3
Order By: Relevance
“…Compared with other malignant tumours, PC cells proliferate rate is slower and it is discovered and diagnosed when urine retention and other symptoms occur [3]. In recent years, the arise of blood prostate specific antigen (PSA) has enhanced the detection rate of inchoate PC [4], but studies have demonstrated that certain organs of human can produce PSA under certain circumstances, the blood PSA lacks the specificity for diagnosing PC [5]. Therefore, there is an urgency to find new indicators for detecting inchoate PC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other malignant tumours, PC cells proliferate rate is slower and it is discovered and diagnosed when urine retention and other symptoms occur [3]. In recent years, the arise of blood prostate specific antigen (PSA) has enhanced the detection rate of inchoate PC [4], but studies have demonstrated that certain organs of human can produce PSA under certain circumstances, the blood PSA lacks the specificity for diagnosing PC [5]. Therefore, there is an urgency to find new indicators for detecting inchoate PC.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumors from the prostate are the leading cause of cancer death among adult males [ 23 ] and the mortality rate from the state de Colima, where this study took place, is one of the highest in the country [ 24 ]. High occurrence of late stages (Gleason score ≥ 7) at the time of diagnosis have been documented, in a population from northern Mexico [ 25 ], and may be determining in the observed mortality.…”
Section: Discussionmentioning
confidence: 99%
“…After venipuncture, the blood was stored, to be subsequently centrifuged (procedure carried out in a balanced way, checking the calibration and matching the tubes according to their physical characteristics) in pairs for 10 min at 3000 rpm, using an Inbrás ALB 18 VT Serological centrifuge (Inbrás, Ribeirão Preto, BRAZ/SP, Brazil), then the serum was transferred with the aid of an automatic pipette and variable volume to a tube properly labeled with a minimum of 2.0 mL of serum, and stored in an ice box and then transferred to the laboratory that performed the sample processing, following the Standard Operating Procedure (SOP) [ 23 ] and ARCHITECT i1000SR immunoassay analyzer (Abbott, Green Oaks, USA/IL, United States of America). A PSA level equal to or greater than 4 ng/mL was considered high [ 13 , 15 , 24 ].…”
Section: Methodsmentioning
confidence: 99%